PERAN ILMU ASTROFOTOGRAFI TERHADAP RUKYATUL HILAL DI ERA DIGITALISASI - Ayunita, Ayunita; Agus , Jasdar (HISABUNA: Jurnal Ilmu Falak, 2025)
Abstract Hilal is an extraterrestrial phenomenon that is very important for humans, especially as a determinant of the calendar system in Islam. In practice, seeing the hilal is not something easy. There are several difficulties encountered such as the hilal which is far from the point of view, weak hilal light and interference from various natural conditions that occur. Along with the development of scientific technology, especially in phalac science, various thoughts have emerged to renew the way to see the hilal using technology, one of which is by using astrophotography techniques. In this study, it aims to determine the existence of astrophotography in the digital era, to determine the implementation of rukyatul hilal in the digital era and to determine the urgency of astrophotography to rukyatul hilal in the digital era.This research uses a type of library research with a descriptive qualitative approach, namely a problem formulation that guides research to explore or portray the social situation to be studied thoroughly. The data sources needed in this research are literature such as; books, journals and previous research, both in the form of primary and secondary sources.This study found that astrophotography plays an important role in the digital era as applied in rukyatul hilal observation. This is evidenced by several rukyat implementing institutions that have begun to use astrophotography techniques. The method of rukyatul hilal observation continues to develop. From seeing with the naked eye to using tools such as location wickets to the digital era now using photography tools that can help clarify and sharpen vision and can capture the observed hilal results. Therefore, the use of astrophotography in rukyatul hilal in the digital era is very necessary because it can help facilitate the observation process, especially in terms of clarifying the object of view and displaying facts realistically, objectively and scientifically so that it can be concluded that the role of astrophotography in rukyatul hilal is a breakthrough in modern technology and information science that can facilitate the implementation of rukyatul hilal because it can be scientifically accounted for with evidence of hilal sightings, so that elements and factors of error and error in the reports of rukyat witnesses can be overcome and can be convincing.